(untitled) (Acta Scientiarum. Biological Sciences, 2023)
The objective of this review is to bring information about innovations and technologies that, through genetic improvement, are being used to improve the sustainability and productivity of agricultural crops, improve human nutrition, as well as conservation and decontamination of soils. Bioremediation consists of using microorganisms that have the ability to modify or decompose certain pollutants, with the possibility of increasing their activity through genetic engineering, building new strains for the transformation of pollutants into inert substances. Genetic improvement is seeking to develop cultivars that are more tolerant to periods of water deficit. Plant biofortification consists of varieties of improved plants that have a higher content of vitamins and minerals, which are obtained through genetic improvement. Thus, biotechnology is once again essential for world agricultural production and can bring a series of other benefits to society.